2018
DOI: 10.1136/bmj.k3322
|View full text |Cite
|
Sign up to set email alerts
|

Renaming low risk conditions labelled as cancer

Abstract: Removing the cancer label in low risk conditions that are unlikely to cause harm if left untreated may help reduce overdiagnosis and overtreatment, argue Brooke Nickel and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 55 publications
0
33
0
1
Order By: Relevance
“…A key next step recommended by panelists was a separate consensus process to establish language that clinicians should use when describing DCIS, although consensus was not achieved on whether to refer to DCIS as something other than cancer. Research has found that significantly more women chose surgery when DCIS was referred to as non-invasive cancer compared with breast lesion or abnormal cells, women are increasingly choosing mastectomy and bilateral mastectomy rather than lumpectomy even though these treatments do not improve breast cancer-specific survival, and clinicians may be driven to over-diagnose and over-treat DCIS due to fear of litigation or missing disease, and feeling compelled to do something rather than nothing [ 45 , 46 ]. Hence, changing the label for DCIS may be a strategy that avoids over-treatment or, until ongoing trials demonstrate the clinical effectiveness of active surveillance for DCIS [ 4 – 6 ], at the very least reduces confusion and anxiety among women diagnosed with DCIS, and concern about explaining DCIS among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A key next step recommended by panelists was a separate consensus process to establish language that clinicians should use when describing DCIS, although consensus was not achieved on whether to refer to DCIS as something other than cancer. Research has found that significantly more women chose surgery when DCIS was referred to as non-invasive cancer compared with breast lesion or abnormal cells, women are increasingly choosing mastectomy and bilateral mastectomy rather than lumpectomy even though these treatments do not improve breast cancer-specific survival, and clinicians may be driven to over-diagnose and over-treat DCIS due to fear of litigation or missing disease, and feeling compelled to do something rather than nothing [ 45 , 46 ]. Hence, changing the label for DCIS may be a strategy that avoids over-treatment or, until ongoing trials demonstrate the clinical effectiveness of active surveillance for DCIS [ 4 – 6 ], at the very least reduces confusion and anxiety among women diagnosed with DCIS, and concern about explaining DCIS among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The counter to this is that a diagnosed cancer (that may otherwise have not caused problems) may lead to unnecessary treatment, further testing, and the psychological consequences of being given a disease label. 17 We don't fully understand how these trade-offs play out in populations of symptomatic patients.…”
Section: Reassuringly Normal?mentioning
confidence: 99%
“…For example it has been suggested to rename DCIS indolent lesions of epithelial origin (IDLE) (19). Other conceptual changes can be found with papilloma and grade 1 carcinoma of the bladder, cervical intraepithelial neoplasia, and non-invasive encapsulated follicular variant of papillary thyroid carcinoma (20). How we define (and how we name) conditions also expands disease.…”
Section: Expanding Definitions (Conceptual)mentioning
confidence: 99%